Una nueva especie de Anochetus (Hymenoptera: Formicidae: Ponerini) de Argentina y Paraguay, asociada con una hormiga cortadora de hojas - González-Campero, María Constanza; Elizalde, Luciana (ENTOMOTROPICA, 2008)
A new species of the ant genus Anochetus is described from Argentina and Paraguay. Anochetus miserabilis González-Campero & Elizalde sp. nov. is included within the emarginatus group, which is distributed in the north of South America and the Antilles. With the inclusion of this new species, the distribution of the group is extended to the south part of South America. Observations of its biology and peculiar association with a leaf cutter ant species are given. In addition, illustrations and a key for the worker caste of the species of the genus present in Argentina and Paraguay are included.